Resources and organization of specialized medical care on the profile "Dermatovenereology" the branch of OJSC "Russian Railways" West Siberian Railway (ZSZHD) - O. A. Karpova (State Scientific Center of Dermatovenereology and Cosmetology, 2017)
The paper presents the results of the comparative analysis of dermatovenerologists service density within West-Siberian railway and territorial entities of Siberian Federal District of Russian Federation. To give an overall characteristic of dermatovenerological service at WSR, a complex assessment of occupied positions, number of individual persons, manning level and the portion of certificated doctors is used.